2006
DOI: 10.1007/s10797-006-6602-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency effects of tax deductions for work-related expenses

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Richter [11], for example, argued that subsidizing commuter traffic would be equivalent to taxing leisure and would thus stimulate labor supply. Borger and Wuyts [12] suggested that public transport subsidies could reduce the car travel demand, parking cost, and congestion issues as an embodiment of positive externalities.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…Richter [11], for example, argued that subsidizing commuter traffic would be equivalent to taxing leisure and would thus stimulate labor supply. Borger and Wuyts [12] suggested that public transport subsidies could reduce the car travel demand, parking cost, and congestion issues as an embodiment of positive externalities.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…The literature on commuting subsidies has largely followed two different strands. First, there is a number of studies which analyse the welfare properties of commuting subsidies, for instance, Brueckner (2003), Richter (2004), and Wrede (2000;2001;. Brueckner (2003) uses a spatial model like ours and finds that subsidising transport is inefficient (see also Fujita, 1989).…”
Section: Introductionmentioning
confidence: 98%
“…1 Focusing on the consumption-leisure choice, Wrede (2000) and Richter (2004) analysed tax deductions for work related expenses within a optimal-taxation framework. Deductions for commuting expenses are possibly second-best efficient if household production (of time) generates non-taxable pure profits.…”
Section: Introductionmentioning
confidence: 99%
“…Wrede (2003), Borck and Wrede (2005) and Richter (2006) provide theoretical contributions on how to design commuting subsidies to be efficient. The only papers considering the efficiency of the Germany's governmental commuting subsidy empirically (Weiss (2009) and Boehm (2013)) both provide evidence for commuting subsidies being efficient.…”
Section: Introductionmentioning
confidence: 99%